Measuring participation: case studies on village land use planning in northern Lao PDR - Lestrelin, Guillaume; Bourgoin, Jeremy; Bouahom, B.; Castella, J.C. (2011)
In the early 1990s, the Lao government launched a nationwide Land Use Planning and Land Allocation programme in a bid to foster socio-economic development while protecting the environment. However, the programme has long been perceived as having negative impacts on rural livelihoods. A central criticism was that limited local participation results in unsustainable land use plans; consequently, the government introduced significant changes into the process to enhance participation. This paper examines the extent to which the evolution of Laos’ village land use planning has resulted in increased local participation and improved livelihoods. Local participation was assessed quantitatively in six study villages, in combination with more qualitative surveys on planning practices and influences on livelihoods and land uses. The analysis reveals that local participation increased only slightly from early planning initiatives until pilot implementation of the revised programme, known as Participatory Land Use Planning. It also shows that (participation in) planning had very limited influence on local land use patterns. Drawing on these findings, the paper explores ways to better translate plans into concrete actions and to effect tangible change in local practices.